An English School for the Welfare State: Literature, Politics, and the University, 1932–1965. (7th June 2016) - Hutton, Alexander
Abstract: Whilst much of the recent focus on modern criticism and the teaching of English Literature in Britain have focused on the work of F. R. Leavis and Scrutiny, this article examines wider conceptions of the English School between the 1930s and 1960s in the figures of L. C. Knights, Bonamy Dobrée, F. W. Bateson, and David Daiches. From the radical political climate of the 1930s and 1940s, there emerged a 'Social Democratic' vision of English teaching within a number of British universities, which attempted to connect teaching and research to the idea that literature provided a remedy to political extremism and the ills of mass society. This vision stressed that the subject was necessary training to create democratic and humane citizens capable of administering and living in a modern welfare state society. The piecemeal reforms to particular departments and wider visions of Knights, Dobrée, Bateson, and Daiches influenced a generation of their pupils and subsequent academics and was instrumental in the creation of new English Departments during the 1960s.